Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1128/jb.185.10.3020-3030.2003
|View full text |Cite
|
Sign up to set email alerts
|

Roles of DegP in Prevention of Protein Misfolding in the Periplasm upon Overexpression of Penicillin Acylase in Escherichia coli

Abstract: Enhancement of the production of soluble recombinant penicillin acylase in Escherichia coli via coexpression of a periplasmic protease/chaperone, DegP, was demonstrated. Coexpression of DegP resulted in a shift of in vivo penicillin acylase (PAC) synthesis flux from the nonproductive pathway to the productive one when pac was overexpressed. The number of inclusion bodies, which consist primarily of protein aggregates of PAC precursors in the periplasm, was highly reduced, and the specific PAC activity was high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
47
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 48 publications
(66 reference statements)
6
47
2
Order By: Relevance
“…In fact, the coexpression of DegP with overexpressed PhoA improved the secretion of this enzyme. Likewise, the enhancement of the production of soluble recombinant penicillin acylase in E. coli via coexpression of DegP has also been demonstrated (20,29).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the coexpression of DegP with overexpressed PhoA improved the secretion of this enzyme. Likewise, the enhancement of the production of soluble recombinant penicillin acylase in E. coli via coexpression of DegP has also been demonstrated (20,29).…”
Section: Discussionmentioning
confidence: 99%
“…Though the protease activity of DegP was shown to be primarily linked with the improvement (23), the possible contribution of the DegP chaperone activity could not be completely excluded. The results suggested that DegP could suppress the physiological toxicity in at least two ways (23). First, it degraded or refolded various abnormal periplasmic proteins generated upon pac overexpression.…”
mentioning
confidence: 93%
“…We previously demonstrated that the presence of exogenous DegP significantly reduced the amount of periplasmic proPAC inclusion bodies and enhanced the production of recombinant PAC in E. coli (19,23). Though the protease activity of DegP was shown to be primarily linked with the improvement (23), the possible contribution of the DegP chaperone activity could not be completely excluded.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When unfolded proteins are accumulated in the periplasm, DegP is induced to clean the periplasm. DegP has also been reported to exhibit chaperone activity (17). However, it is not clear why only NlpE among the lipoproteins induces DegP.…”
mentioning
confidence: 98%